Espiritualidade educativa em Leonardo Boff: construtividade e sustentabilidade bioglobal - Freitas, Francel dos Santos Marzork de (2014)
This conclusion paper for the Professional Master s program in Theology has as its goal to analyze the thought of the Brazilian thinker Leonardo Boff in its theological and ecological implications, and to list possibilities for a style of ecclesiastical community education which values the intersubjective relations between human beings and of these with nature and with the cosmos. Boff is an interdisciplinary thinker who dialogs with the social sciences and with the knowledge coming from the natural sciences as well as with the Franciscan mysticism. That is why his thinking provides the broadest and most relevant possible perspectives relating to the themes dealing with what is being called planetary awareness . This is a form of perception in which life in community needs a respect for nature beyond a simple maintenance of an ecological status, one which above all is guided by dialog in action or better put: by the inter-relationality of the I and the You with the This, according to the contextual needs.